Suppose $X$ is an exponential random variable with mean $2$, and $Y$ is an exponential random variable with mean $3$. I want to write the density function for $X-Y$. Now, I know (at least, I'm pretty sure) that this is calculated by the formula:

$f_{X-Y}(z)=\displaystyle\int_{-\infty}^\infty f_X(y)f_Y(y-z)\,dy$,

but I have a hard time with the actual calculation. The trouble is that both $f_X$ and $f_Y$ have support $[0,\infty)$, and that makes me confused about when the expression $f_Y(y-z)$ is defined.

To be clear, I have the density functions:

$f_X(y)=\frac12e^{-y/2}$, $f_Y(y)=\frac13e^{-y/3}$, both for $y\ge 0$.

I hope my question makes sense; thanks in advance.

  • Yes, the integrals can be simplified to consider only $y \geq 0$ (so that $f_X(y) >0$) and $y - z \geq 0$ (so that $f_Y(y-z)>0$). Since $z$ is a constant and $y$ is the integration variable, it means $\int_{y= \max[0,z]}^{\infty}$. – Michael Dec 19 '16 at 3:07
  • So if we assume $z\geq 0$, then $y$ takes values of all real numbers greater than or equal to $z$. Remember that, with respect to the integral, $z$ is a constant and does not change, while $y$ is the integration variable. – Michael Dec 19 '16 at 3:10
  • 1
    The difference of two independent exponentials is a Laplace distribution. Have a look at… – A.G. Dec 19 '16 at 3:11
  • 2
    It looks like this question has come up previously,… – jjet Dec 19 '16 at 3:12
  • @A.G. Only the weighted difference has Laplace distribution. – msm Dec 19 '16 at 5:11
up vote 2 down vote accepted

We are convolving $X\sim f_X(x)={\frac{1}{2}e^{-x/2}}$ supported on ${[0,\infty)}$ with $-Y\sim f_{-Y}(y)={\frac{1}{3}e^{y/3}}$ supported on ${(-\infty,0]}$. Now consider the graphical representations for convolution of these two exponential functions. We fix the former and move the mirrored of the latter with respect to the $y$-axis: $$f_Z(z)=\int_{-\infty}^{\infty}\color{blue}{f_X(\tau)}\color{red}{f_{-Y}(-\tau+z)}d\tau$$

When $z<0$:

enter image description here $$\begin{align} f_Z(z)&=\int_0^\infty\frac{1}{2}e^{-\tau/2}.\frac{1}{3}e^{(z-\tau)/3}\mathrm d\tau\\ &=\frac{e^{z/3}}{6}\int_0^\infty e^{-5\tau/6}\mathrm d\tau\\ &=\frac{e^{z/3}}{6}\left(\frac{-6}{5}\right)(0-1)\\ &=\frac{1}{5}e^{z/3} \end{align}$$

When $z>0$:

enter image description here

$$\begin{align} f_Z(z)&=\int_z^\infty\frac{1}{2}e^{-\tau/2}.\frac{1}{3}e^{(z-\tau)/3}\mathrm d\tau\\ &=\frac{e^{z/3}}{6}\int_z^\infty\frac{1}{6}e^{-5\tau/6}\mathrm d\tau\\ &=\frac{e^{z/3}}{6}\left(\frac{-6}{5}\right)(0-e^{-5z/6})\\ &=\frac{1}{5}e^{-z/2} \end{align}$$

  • The pictures are really helpful! I've never seen convolution depicted graphically before; that really clarifies the domains. – G Tony Jacobs Dec 19 '16 at 22:22
  • 1
    More intuitive illustration of convolution [of two other functions]. – msm Dec 19 '16 at 22:48

To get the formula for $f_Z$ consider $$\begin{align} \mathbb{P}(X-Y<z)& =\iint _{x-y<z} f(x,y)\mathrm{d}x\mathrm{d}y \\ &= \frac 16 \iint_{x < z+y} e^{-y/3}e^{-x/2}\mathrm{d}x\mathrm{d}y \end{align}$$ Now, to find the region of integration, we know that $0<x<\infty$ and $0<y<\infty$, from the above we also know that $0<x<z+y$, and therefore $\max (-z,0) <y < \infty$. From here we get two cases $$ 0<y \quad \mathrm{and} \quad 0<z$$ $$-z<y \quad \mathrm{and} \quad z<0$$ $$\mathbb{P}(X-Y<z)=\frac 16 \int_0^{\infty}\int_0^{z+y} e^{-y/3}e^{-x/2}\mathrm{d}x\mathrm{d}y$$ For positive $z$ and $$ \mathbb{P}(X-Y<z)=\frac 16 \int_{-z}^{\infty}\int_0^{z+y}e^{-y/3}e^{-x/2}\mathrm{d}x\mathrm{d}y$$ For negative $z$. These integrals give $$1-\frac 25 e^{-z/2} $$ and $$\frac 35 e^{z/3} $$ Respectively, differentiate to get the PDF $$ f_Z(z) = \frac 15 \cases{e^{-z/2} & if $z > 0$\cr e^{ z/3} & if $z < 0$\cr}$$

In the general case, suppose $X$ and $Y$ are independent exponentially distributed random variables with rate parameters $a$ and $b$; thus $$f_X(x) = a e^{-ax} \mathbb 1(x > 0), \quad F_X(x) = (1 - e^{-ax})\mathbb 1(x > 0), \\ f_Y(y) = b e^{-by} \mathbb 1(y > 0), \quad F_Y(y) = (1 - e^{-by})\mathbb 1 (y > 0).$$ Then the CDF of $Z = X - Y$ is $$\begin{align*} F_Z(z) &= \Pr[X - Y \le z] \\ &= \int_{y=-\infty}^\infty \Pr[X \le z + y] f_Y(y) \, dy \\ &= \int_{y=-\infty}^\infty (1 - e^{-a(z+y)}) be^{-by} \mathbb 1 (z+y > 0) \mathbb 1 (y > 0) \, dy \\ &= \int_{y = \max(0,-z)}^\infty be^{-by} - e^{-az} be^{-(a+b)y} \, dy \\ &= \left[-e^{-by} + \frac{b e^{-az} e^{-(a+b)y}}{a+b}\right]_{y=\max(0,-z)}^\infty \\ &= \left(\frac{e^{a\max(0,-z)}}{b} - \frac{e^{-az}}{a+b}\right) b e^{-(a+b) \max(0,-z)}. \end{align*}$$ When $z < 0$, $\max(0,-z) = z$, and we get $$F_Z(z) = \frac{ae^{bz}}{a+b}.$$ When $z \ge 0$, $\max(0,-z) = 0$ and we get $$F_Z(z) = 1 - \frac{be^{-az}}{a+b}.$$ Therefore, the CDF can be written piecewise as $$F_Z(z) = \begin{cases} \frac{ae^{bz}}{a+b}, & z < 0 \\ 1 - \frac{be^{-az}}{a+b}, & z \ge 0.\end{cases},$$ with the PDF $$f_Z(z) = F'_Z(z) = \frac{ab}{a+b} \begin{cases} e^{bz}, & z < 0 \\ e^{-az}, & z \ge 0. \end{cases}.$$

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.